Arthur Nikisch autograph quotation from Beethoven's Fifth Symphony - Nikisch, Arthur, 1855-1922:::Creator:::::::::::: (2021)
Autograph manuscript signed by Arthur Nikisch with his inscription of the opening four bars of Beethoven's Fifth Symphony, op. 67.